Separation of Glycerol from Biodiesel Oil Products Using High Voltage Electrolysis Method - Lety Trisnaliani; Ahmad Zaki (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
This study aims to separate glycerol from used cooking oil biodiesel products. This research is done by main process by analyzing free fatty acid level (FFA) to know the fat content of the oil in order to know the next process. This research is done by electrolysis process using high voltage. We done transesterification process by using methanol and NaOH as catalyst before performing the process of electrolysis with high voltage. Biodiesel is manufactured using a mini-scale stirred tank reactor (RATB) laboratory. This process is heated at temperature (35-60) oC, the ratio of used cooking oil and methanol (5:1, 6:1, 7:1, 8:1, 9:1) using a 0.1 N NaOH catalyst. The research obtained optimum reaction temperature yield highest percentage of rendement at temperature 60oC and ratio of used cooking oil and methanol 5:1 with percentage of rendement equal to 88,88, cetane number 48,4, kinematic viscosity 2,560, pour point 37,4 oF, flash point 131 oF, Conradson Carbon Residue (CCR) 0.09, and ASTM Colour 1.5. This shows that the manufacture of biodiesel with high microwave and high voltage utilization yields a high percentage of 88.88 and the product is biosolar-48.